FENOMENA PENYALAHGUNAAN POTRET SESEORANG SEBAGAI STIKER WHATSAPP DI KALANGAN GENERASI Z DALAM KOMUNIKASI DIGITAL - Gabriella Lidya (Busyro: Jurnal Dakwah dan Komunikasi Islam, 2024)
There is abuse of WhatsApp users who make stickers with other people's faces to be used as ridicule or provocation. For users who use the sticker it may feel legitimate, but it is not known what impact this will have on victims who experience this abuse. The purpose of this study is to provide an in-depth view and understanding of how the misuse of stickers in digital communication can affect users' social lives and provide a foundation for users, especially among generation Z. Researchers in the process of preparing this article apply descriptive-based qualitative reviews as a type of research that produces data sets in the form of documentation, strings of words, or images so as not to use numbers in answering Hypothesis. Results showed more experiences of individuals who were less accepting of themselves as victims who were used as stickers by other individuals. However, it cannot be denied that Whatsapp stickers are needed to communicate digitally, knowing the reaction or meaning of the message conveyed can be seen by the sticker shared. Keywords: Digital Communication, Portrait of a Person, Generation Z, Whatsapp Stickers